Consumo e identidades de trabalhadoras rurais pomeranas e quilombolas do sul do Brasil - Borges, Gabriela Schmalfuss (2023)
The present study is carried out with rural workers of Pomeranian and Quilombola origin, living in São Lourenço do Sul/RS. Through qualitative empirical research, we seek, as a general objective, to interpret what is the image that this group of women has of what a rural woman is and what is the impact of the representation constructed from television media and the internet on self-representation mediated by sociability, identity and their networks as rural workers. For this, we used the methodology of Sociological Portraits, proposed by Bernard Lahire (2004), which enables the understanding of the interlocutors' life trajectories, and how they consume and interact with the media. The research is in line with the field of cultural studies, specifically, the theory of social uses of the media, by Jesús Martín-Barbero (1997, 2018), in view of the interweavings that the author proposes between culture and media products in everyday life of individuals. As a result, we noticed that both Pomeranians and Quilombolas consider that the image of rural women shown by the media is someone suffering and hardworking, with white skin. While the Pomeranians do not identify with this representation due to the denial of their class and because they seek to link themselves to higher economic strata, the Quilombolas do not identify themselves due to their color, and consequently, they feel represented by images of black women urban. From the interviews, we also found that the media fulfill different roles within each community, and can be seen as a distraction or as a space for learning and inspiration. Likewise, we note the central role that digital social networks, especially Facebook, play in the way in which the interlocutors choose to represent themselves. The Pomeranians exalt work in the fields and seek to demonstrate a possible connection with agribusiness and large producers. Quilombolas, on the other hand, show the leadership roles they occupy in the black movement. Also on Facebook, women from both communities exalt motherhood and the importance of family. With regard to media consumption, attention is drawn to the consolidation of the internet in rural areas, with its use linked to work and leisure activities of all research participants.